Antithesis to Machismo in the Poetry of Parijat and Kundan Sharma - Niroula, Dhundi Raj (Humanities and Social Sciences Journal, 2021)
This research paper tries to provide an analysis, from the feministic approach, of the Nepali modernist poetry written by Parijat and Kundan Sharma. They were the avant-garde female poets of the 1960s in Nepali literature to write on the gender issues threatening the patriarchal system. Their antithetical stand to machismo was inspired by the Western academic and literary tradition. Some of the women characters in Parijat's poems are found to have been sufferer under triple marginalization, namely, from the perspectives of economic status, caste and gender. In spite of the fact that the society in the 1960s was inhospitable to gender equality and women's rights, these poets brilliantly articulated agonizing experiences of gender bias pervasive in both textual and practical world. Undoubtedly, the preliminary moderate feministic voice in Nepali poetry initiated by Parijat and Kundan played a significant role to deconstruct myths about women institutionalized by text, tradition and socio-cultural context. Unlike the usual reading, this study shows how these two pioneer female poets initiated revolutionary zeal to defy status quo based on traditional gender role.